1995
DOI: 10.1002/etc.5620140920
|View full text |Cite
|
Sign up to set email alerts
|

Use of joint toxic response to define the primary mode of toxic action for diverse industrial organic chemicals

Abstract: An important aspect of understanding how multiple toxicants jointly act involves defining the primary mode of toxic action for the chemicals of interest. We have explored the use of 96‐h acute toxicity tests with juvenile fathead minnows and primarily binary chemical mixtures to define the primary acute mode of toxic action for diverse industrial organic chemicals. Our investigation mainly considered the two special cases of noninteractive joint action known as concentration (simple similar) and response (inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(94 citation statements)
references
References 39 publications
3
87
1
Order By: Relevance
“…These fi ndings indicate the complex nature of the underlying mechanisms by which organ-isms tolerate exposure to mixtures of xenobiotics in their environment. Therefore, it is likely that the toxicity of a pesticide mixture is more complex than a simple "con centration addition" or a "response addition" model typically used for predicting the potential impact of mixtures in aquatic systems (Broderius et al, 1995;McCarty et al, 1992;Dawson and Wilke, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings indicate the complex nature of the underlying mechanisms by which organ-isms tolerate exposure to mixtures of xenobiotics in their environment. Therefore, it is likely that the toxicity of a pesticide mixture is more complex than a simple "con centration addition" or a "response addition" model typically used for predicting the potential impact of mixtures in aquatic systems (Broderius et al, 1995;McCarty et al, 1992;Dawson and Wilke, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of erythrocyte superoxide dismutase in human erythrocytes decreased with the increasing dose of 2,4-DCP, whereas glutathione peroxidase activity increased at about 250 ppm (Bukowska, 2003). In the former studies, the LC50 value of 2,4-DCP for fish ranged from 7.0 to 11.6 mg/L were reported (Phipps et al, 1981;Broderius et al, 1995;Kishino and Kobayashi, 1996), and the no-observed-effects concentration (NOEC) of acute toxicity in medaka was 3.3 mg/L (Kondo et al, 2005). Some studies reported that 2,4-DCP affects in vitro administration causes changes in glutathione and antioxidant enzyme activities (Bukowska et al, 2003(Bukowska et al, , 2007.…”
Section: Introductionmentioning
confidence: 92%
“…However, the M value of nitrobenzene combined with 1,3-methylbenzene (1.660) was highest, showing a partially additive effect ( (Table 5). According to the study of Broderius [17], concentration addition is characterized by M = 1 ± 0.2, where M < 0.8 represents synergism and M > 1.2 indicates antagonism. Thus, 31.57% of 19 substituted benzenes showed synergistic effects and additive effects, while 36.84% of these compounds showed antagonistic effects.…”
Section: Binary Substituted Benzene Toxicitymentioning
confidence: 99%